Selected reading from Rizal - Rizal, Jose; Bassig, Ricardo C. (Manila : Merriam School & Office Supplies Co., 1959)
This diminutive volume has been published in response to a felt need occasioned by the implementation of Republic Act No. 1425, which calls for the inclusion of the writings of Dr. Jose P. Rizal. in the curricula of all public and private schools, colleges, and universities. It is especially intended for the use of secondary schools where the course on Rizal is integrated with English Literature or social sciences.
Rizal's autobiography -- Along the Pasig -- Our Mother Tongue -- My First inspiration -- Congratulations -- Memories of Calamba -- To the child Jesus -- Hymn to Magellan's fleet -- To education -- The Intimate alliance between religion and education -- Through education our Motherland receives light -- To the Filipino youth -- To the virgin Mary -- Farewell to Leonor -- You ask me for verses -- To Miss C.O.y.R -- Hymn to labor -- To the flowers of Heidelberg -- The Song of Maria Clara -- To my Muse -- Hymn to Talisay -- My retreat -- To Josephine -- The Song of the traveler -- My last farewell -- Love of country -- Luna and Hidalgo - a comparison -- Rizal's letter to his mother -- Rizal's letter to his Trinidad -- Rizal's letter to his brother Paciano -- Rizal's letter to his countrymen -- From Rizal's diary -- Rizal's retraction
Includes bibliographical references.
Keywords: RIZAL, JOSE - 1861-1896; RIZAL, JOSE - 1861-1896 -- BIOGRAPHY